Application of Tarbawi Tafsir Principles in the Formation of Islamic Personality in Schools - Teten Mulyana; Iskandar Mirza (Penerbit Hellow Pustaka, 2025)
The application of Tarbawi's Tafsir principles in the formation of Islamic personalities in schools is a strategic effort to integrate the values of the Qur'an and Hadith in students' character education. Tafsir Tarbawi, which emphasizes the development of noble morals and strong faith, aims to form students who are not only academically intelligent, but also have noble Islamic character. This article examines various ways to apply the principles of Tarbawi Tafsir in the educational environment, including by instilling correct aqidah values, introducing noble morals through teaching the Koran and Hadith, and using interactive and contextual learning methods to connect Islamic teachings with students' daily lives. Tarbawi Tafsir-based learning also invites students to apply Islamic teachings in daily behavior, both at school and at home. In this research, a qualitative approach was used with literature studies and observations in several schools that implemented Tafsir Tarbawi. The results showed that the application of this principle in schools succeeded in increasing students' understanding of Islamic teachings, as well as strengthening their character in facing life's challenges. Collaboration between teachers, parents and the community is also very important to create an Islamic educational environment and support the development of students' personalities. Overall, the application of Tafsir Tarbawi has great potential in forming a young generation with noble character and an Islamic personality.